2021
DOI: 10.3847/1538-4365/abf4d1
|View full text |Cite
|
Sign up to set email alerts
|

The Old Moving Groups in the Field of Taurus

Abstract: In this work, we present a systematic search for stellar groups in the Taurus field by applying the DBSCAN algorithm to the data from Gaia DR2. We find 22 groups, consisting of 8 young groups (Groups 1–8) at ages of 2–4 Myr and distances of ∼130–170 pc, and 14 old groups (Groups 9–22) at ages of 8–49 Myr and distances of ∼110–210 pc. We characterize the disk properties of group members and find 19 new disk-bearing stars, 8 of which are in the young groups with 11 others belonging to the comparatively old group… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…In a Gaia DR2 study of the Orion OB association, Zari et al (2019) found that multiple star-forming events occurred and led to the subgroups. In a search for stellar groups in the Taurus field, Liu et al (2021) identified eight groups younger than ∼4 Myr and 14 older groups (8-49 Myr). In a smaller region, Esplin & Luhman (2022) found older stars in Corona Australis and inferred a past burst of star formation, likely related to the ongoing star formation in the Coronet cluster.…”
Section: Dynamics Of the Subclusters In And Around The Serpens Molecu...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a Gaia DR2 study of the Orion OB association, Zari et al (2019) found that multiple star-forming events occurred and led to the subgroups. In a search for stellar groups in the Taurus field, Liu et al (2021) identified eight groups younger than ∼4 Myr and 14 older groups (8-49 Myr). In a smaller region, Esplin & Luhman (2022) found older stars in Corona Australis and inferred a past burst of star formation, likely related to the ongoing star formation in the Coronet cluster.…”
Section: Dynamics Of the Subclusters In And Around The Serpens Molecu...mentioning
confidence: 99%
“…Stars formed in previous bursts are often still located in small subclusters, while some have been dispersed throughout the cloud or were born in small groups. In many clouds the older stars are not colocated with the youngest stars, indicating that the site for star formation changes with time within a cloud complex (e.g., Getman et al 2014aGetman et al , 2014bKounkel et al 2018;Kristensen & Dunham 2018;Vázquez-Semadeni et al 2018;Liu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We employ the Density-Based Spatial Clustering of Applications with Noise (DBSCAN; Ester et al 1996) algorithm to detect discrete subclusters of stars in the datasets, chosen for this work as it tends to be favoured by observers to quantify structure in cluster regions (Gao 2014, Bhattacharya et al 2017, Joncour et al 2019, Zari et al 2019, Anais Vilchez et al 2020, Gao et al 2021, Liu et al 2021, Gao et al 2021) perhaps because it offers several advantages over other well-established clustering algorithms. First, it does not require a priori knowledge of the number of clusters in a region as this is determined by the algorithm itself.…”
Section: Dbscanmentioning
confidence: 99%
“…In a Gaia DR2 study of the Orion OB association , Zari et al (2019) found in that multiple star-forming events occurred and leaded to the subgroups. In a search for stellar groups in the Taurus field, Liu et al (2021) identified 8 groups younger than ∼ 4 Myr and 14 older groups (8-49 Myr). In a smaller region, Esplin & Luhman (2022) found older stars in Corona Australis and inferred a past burst of star formation, likely related to the ongoing star formation in the Coronet Cluster.…”
Section: Dynamics Of the Subclusters In And Around The Serpens Molecu...mentioning
confidence: 99%
“…Stars formed in previous bursts are often still located in small subclusters, while some have been dispersed throughout the cloud or were born in small groups. In many clouds the older stars are not co-located with the youngest stars, indicating that the site for star formation changes with time within a cloud complex (e.g., Getman et al 2014b,a;Vázquez-Semadeni et al 2018;Kounkel et al 2018;Kristensen & Dunham 2018;Liu et al 2021).…”
mentioning
confidence: 99%